Effect of Polyvinyl Alcohol Ligands on Supported Gold Nano-Catalysts: Morphological and Kinetics Studies - Stefano Scurti; Eleonora Monti; Elena Rodríguez-Aguado; Daniele Caretti; Juan Antonio Cecilia; Nikolaos Dimitratos (Nanomaterials, 2021)
The effect of polyvinyl alcohol (PVA) stabilizers and gold nanoparticles supported on active carbon (AuNPs/AC) was investigated in this article. Polymers with different molecular weights and hydrolysis degrees have been synthesized and used, like the stabilizing agent of Au nano-catalysts obtained by the sol-immobilization method. The reduction of 4-nitrophenol with NaBH4 has been used as a model reaction to investigate the catalytic activity of synthesized Au/AC catalysts. In addition, we report several characterization techniques such as ultraviolet-visible spectroscopy (UV-Vis), dynamic light scattering (DLS), X-ray diffraction (XRD), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS) in order to correlate the properties of the polymer with the metal nanoparticle size and the catalytic activity. A volcano plot was observed linking the catalytic performance with hydrolysis degree and the maximum of the curve was identified at a value of 60%. The Au:PVA-60 weight ratio was changed in order to explain how the amount of the polymer can influence catalytic properties. The effect of nitroaromatic ring substituents on the catalytic mechanism was examined by the Hammett theory. Moreover, the reusability of the catalyst was investigated, with little to no decrease in activity observed over five catalytic cycles. Morphological and kinetic studies reported in this paper reveal the effect of the PVA polymeric stabilizer properties on the size and catalytic activity of supported gold nanoparticles.